Dynamic analysis of flexible hoisting rope with time-varying length - Ji-hu Bao; Peng Zhang; Chang-ming Zhu (Прикладная механика, 2015)
The governing equations of flexible hoisting rope are developed employing Hamilton’s principle. Experiments are performed. It is found that the experimental data agree with the theoretical prediction very well. The results of simulation and experiment show that the flexible hoisting system dissipates energy during downward movement but gains energy during upward movement. Further, a passage through resonance in the hoisting system with periodic external excitation is analyzed. Due to the time-varying length of the hoisting rope the natural frequencies of the system vary slowly, and transient resonance may occur when one of frequencies coincides with the frequency of external excitation.